The Effect of Work Discipline, Work Motivation, and Job Satisfaction on Employee Performance at PT ABC - Siburian, Debrina Hotmasi; Natalia, Jesika; Sipayung, Shelly; Anam, Yeninda (Universitas Pelita Harapan, 2023)
Employee performance is an important aspect for the company as an effort in achieving the company's targets and goals through empowering its employees. Performance can be formed from several factors, such as discipline, motivation, and performance job satisfaction. This study aims to determine the effect of discipline work, work motivation and job satisfaction at PT ABC. Number of samples that determined as many as 55 respondents and data processing using the PLS-SEM technique with SmartPls software. The research results obtained are that 1) Work discipline has a positive effect on employee performance at PT ABC; 2) Work motivation has a positive effect on employee performance at PT ABC; 3) Job satisfaction has a positive effect on employee performance at PT ABC.